BOOK PUBLISHING IN LITHUANIA DURING NAZI OCCUPATION (1941–1944) - KOSAKOVSKAJA, JEKATERINA (Knygotyra, 2011)
Scientists have devoted substantial attention to the period of the second occupation of Lithuania. However, the issue of book publishing, printing and distribution during the period hereinbefore mentioned was covered in outline until now. The purpose of the article is to comprehensively highlight different aspects of book publishing in Lithuania, including Nazis’ illegal actions and high-handed behaviour towards Lithuanian publishing and printing houses and the brave attempts of the latter to protect and maintain the publishing of books. Particular attention is given to social, cultural and political processes involved in book publishing, printing and distribution. The Nazi controlled the whole process of publishing, from the check of a book’s contents to the distribution. Nonetheless, there were published many books important for the Lithuanian culture, owing to the courage and wit of publishers, printers, readers and others who cherished books and realized their value for the coming generations. The chronological limits of the research were fixed between the second half of 1941 and the second half of 1944 inclusive, and the territory covered the Vilnius region regained in 1939, but did not cover the Klaipėda region annexed the same year. The bibliographical periodical “Bibliografijos žinios” published in 1941–1943 as well as a significant collection of different administrative documents belonging to the publishing house “Valstybine leidykla” and books published in 1941–1944, kept in the National Martynas Mažvydas library, should be considered the most valuable sources of the printed heritage of the period. It is exactly these sources that were mainly used to make a comprehensive bibliographical listing of books published during the Nazi occupation of Lithuania, an accurate statistical analysis due to which it was possible to assess the publishing tendencies.
Keywords: ...